Sanitation Quality of Decks and Passenger Cabins on Passenger Ships at Samarinda Port - Rico Fernando Agaki Adadikam; Blego Sedionoto; Riyan Ningsih (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : Passenger ships play an essential role in transportation across eastern Indonesia. However, poor sanitation and hygiene conditions onboard can increase the risk of environmental disease transmission, especially in confined spaces with limited air circulation and clean water supply. Objective : This study aimed to describe the sanitation quality of decks and passenger cabins on passenger ships arriving and departing from Samarinda Port, East Kalimantan. Research Methods/ Implementation Methods : This research used a quantitative descriptive method with an observational approach. The study was conducted on three passenger ships KM. Aditya, KM. Prince Soya, and KM. Queen Soya. The observed variables included deck sanitation and passenger cabin sanitation using a ship sanitation observation checklist. Data were collected twice, during ship arrival and before departure, and analyzed univariately to determine the frequency distribution of sanitation conditions. Results : The results showed that upon arrival, only one ship (33.3%) met the deck sanitation requirements, while two ships (66.7%) did not. All ships (100%) failed to meet sanitation standards for passenger cabins. However, before departure, all ships (100%) complied with sanitation requirements for both decks and passenger cabins. This indicates a significant improvement after routine cleaning was conducted prior to departure. Conclusion/Lesson Learned : The sanitation conditions of passenger ships at Samarinda Port remain inadequate upon arrival but improve after pre-departure cleaning. Continuous supervision, daily maintenance, and routine inspections are necessary to maintain ship hygiene and prevent disease transmission in the ship environment.